PENGARUH KETEBALAN IRISAN CHIPS SINGKONG DAN LAMA FERMENTASI TERHADAP SIFAT FISIKO KIMIA TEPUNG MOCAF (MODIFIED CASSAVA FLOUR) - Sohib Assalam; Novian Wely Asmoro; A. Intan Niken Tari; Sri Hartati (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2019)
Modified cassava flour or mocaf is cassava flour which has been modified using the principle of lactic acid bacteria fermentation. One factor that needs to be observed is the fermentation process which will affect the quality of the mocaf flour produced. This study aims to determine the effect of cassava chip slice thickness and fermentation time in the process of making mocaf flour on physico-chemical quality of mocaf flour. The research method used Factorial RAL with 2 treatment variables, namely the thickness of cassava chips slices (0.5 cm, 1 cm, 1.5 cm) and fermentation time (24 hours and 48 hours), resulting in 6 treatment combinations and repeated 3 replications , so there are 18 experimental units. The data obtained was processed by Analysis of Variance (ANOVA) using SPSS 22 software. If the ANOVA test results stated that the samples tested were significantly different, then DMRT (Duncan Multiple Range Test) was carried out at the 0.05 confidence level. Based on statistical analysis shows that there is no interaction between the thickness treatment of cassava chips and the length of fermentation. Meanwhile, the slice thickness had a significant effect (P˂0.05) on water content and swelling power of mocaf flour, but did not significantly influence (P0.05) on the solubility index in mocaf flour water. The duration of fermentation had a significant effect (P˂0.05) on moisture content and swelling power of mocaf flour, but had no significant effect (P˃0.05) on the solubility index in mocaf flour water. The yield of mocaf flour obtained ranged from 30.47% - 32.98% with the lowest moisture content of 10.31%. The average swelling power of mocaf flour is 12.24 g / g and the average water solubility index is 5.29%.Keywords: Chips, Thickness, Fermentation Time, Mocaf Flour